Financial Literacy and the Indonesian Standard Quick Response Code (QRIS) Effectiveness on the Performance of MSMEs in South Jakarta - Elsa Dewi Farantika; Darto Darto (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to analyze the effect of financial literacy and the effectiveness of using the Indonesian Standard Quick Response Code (QRIS) on the performance of Micro, Small, and Medium Enterprises (MSMEs) in South Jakarta. The research employs a quantitative approach with a correlational design. Data were collected through Likert-scale questionnaires distributed to 70 MSME owners who have adopted QRIS, selected using a purposive sampling technique. Data analysis was conducted using multiple linear regression, preceded by validity, reliability, and classical assumption tests. The results indicate that financial literacy has a positive and significant effect on MSME performance (β = 0.405; t = 3.833; p < 0.001). The effectiveness of QRIS also shows a positive and significant effect on MSME performance, with a more dominant influence (β = 0.473; t = 4.441; p < 0.001). The coefficient of determination (R²) of 0.523 indicates that financial literacy and QRIS effectiveness jointly explain 52.3 percent of the variance in MSME performance. Therefore, enhancing financial literacy and optimizing the use of QRIS are strategic factors in improving MSME performance in urban areas. This study provides empirical contributions to the MSME management literature by strengthening the role of financial literacy and digital payment systems, and it serves as a reference for policymaking in MSME development within the digital economy era.